Study on behaviour of different shapes and locations of opening on reinforced concrete beam by using ANSYS - Yep, Kar Mun (2018)
Nowadays, the construction of modern building requires services ducts and piping in order to accommodate essential services such as air-conditioning, electricity, water piping, fire sprinkle and others utility. The existence of a web opening on R.C beam will affect the overall behaviour of the beam and will eventually affect the serviceability and ultimate limit state of the building. The aim of this research is to determine the effect of various locations and shapes of opening of RC beam in term of ultimate load, deflection and crack pattern. The study is about the finite element analyses on beam with webs opening with 4 point bending test by using ANSYS 12 software. There are total of 6 models were analysed in this study. A solid R.C beam model, SB was used as controlling model, which is a reinforced concrete beam without any opening. There are 5 models with openings were analysed and there were different in the shape of opening and the location of the opening. The location of the openings distinguished into 240mm, 480mm and 910mm from the edge of beam labelled as BO1, BO2 and BO3 respectively. Moreover, the shapes of opening are categorized as circular, square and rectangular while keeping the area and location of opening unchanged. The square opening is designated as BO4 and the rectangular opening is designated as BO5. By the analysis, the greatest deflection is occurring in the mid-span of the beam. Moreover, in the term of ultimate load, opening that located near support show the greatest reduction in ultimate load, 55.66% comparing with solid beam whereas circular opening gives the greatest value of deflection compare with square opening and rectangular opening.